1990
DOI: 10.1203/00006450-199001000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Ventilation and Barotrauma on Pulmonary Clearance of 99mTechnetium Diethylenetriamine Pentaacetate in Lambs

Abstract: ABSTRACT. We studied the effect of positive pressure mechanical ventilation on the pulmonary clearance (k) of 99mtechnetium diethylenetriamine pentaacetate (99mTc-DTPA) in lambs. Twelve lambs were anesthetized and ventilated with air at 25 breathslmin and with end expiratory airway pressure at 2 cm H20 for a minimum period of 8 h. Four lambs received normal pressure ventilation with peak airway pressure at 17 f 3 cm Hz0 and eight received high pressure ventilation with peak airway pressure at 41 f 2 cm H20. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Barotrauma was initially thought to be the major contributing factor leading to lung injury [2]. However, studies from the 1980s showed that volutrauma is a major cause of lung injury [3,4].…”
Section: Invasive Ventilation Modes Pressure Versus Volume Targeted Vmentioning
confidence: 99%
“…Barotrauma was initially thought to be the major contributing factor leading to lung injury [2]. However, studies from the 1980s showed that volutrauma is a major cause of lung injury [3,4].…”
Section: Invasive Ventilation Modes Pressure Versus Volume Targeted Vmentioning
confidence: 99%
“…Another possible explanation could be the effect of mechanical ventilation on lung tissue. In an experimental animal model, it has been demonstrated that volume‐controlled ventilation significantly increases the amount of alveolar macrophages recovered by lavage in intact lungs after 8 h of mechanical ventilation [26]. It is well known that macrophages, together with neutrophils, are active oxygen‐consuming cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…As the epithelium is progressively stretched during static inflation there is a non‐reversible opening of water‐filled channels between alveolar cells resulting in free diffusion of small solutes and even albumin across the epithelial barrier (Egan et al. , 1976; Kim & Crandall, 1982; Ramanathan et al. , 1990).…”
Section: What Did We Learn From Animal Experiments On Ventilator‐indumentioning
confidence: 99%
“…Effects of overinflation on epithelial permeability have been studied in fluid-filled in situ lobes, to exclude the effect of surface tension. As the epithelium is progressively stretched during static inflation there is a non-reversible opening of water-filled channels between alveolar cells resulting in free diffusion of small solutes and even albumin across the epithelial barrier (Egan et al, 1976;Kim & Crandall, 1982;Ramanathan et al, 1990). Such changes were shown to occur only at high distending pressures and have been attributed to peak inspiratory epithelial overstretching which occurs as a result of inflation in the supra-physiological range only (Kim & Crandall, 1982).…”
Section: Disturbed Fluid Balance Over the Epithelial Barrier Caused Bmentioning
confidence: 99%